Peningkatan Mutu Perguruan Tinggi Kegamaan Islam Melalui Penyusunan Manajemen Strategis Dengan Pendekatan Balanced Scorecard: Studi Kasus di STAI Sangatta Kutai Timur - Zamroni Zamroni; Siti Nasiah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2018)
College has an important role in nation building. Therefore, university governance systems need to get serious attention and appropriate management touches. One of the modern management concepts that can be used is balanced scorecard, which is expected to improve the quality of the institution. This research uses qualitative approach of case study type with research setting at STAIS Sangatta Kutai Timur. The results showed that; improvement of education quality in STAIS Sangatta Kutai Timur is done through; 1) visionary leadership, 2) internal and external environmental analysis done with SWOT analysis, 3) to make quality as